Profitability, Leverage, and Tax Avoidance: Evidence from Earnings Management - Sekar Martania Nurhayati; Gianifa Zahra Salsabhila; Imam Hadiwibowo (Jurnal Proaksi, 2026)
Main Purpose - This study aims to examine the effects of profitability, leverage, and tax avoidance on earnings management in insurance subsector companies listed on the Indonesia Stock Exchange (IDX) during the 2019-2023 period. Method - This study employs a quantitative approach using secondary data from annual financial statements. Purposive sampling yielded six companies with 30 observations. Earnings management is measured using discretionary accruals based on the Modified Jones Model, profitability using ROA, leverage using DAR, and tax avoidance using CETR. The data were analyzed using multiple linear regression with SPSS 27. Main Findings - The results show that profitability has a positive effect on earnings management, as higher profits may encourage management to maintain performance. Meanwhile, leverage and tax avoidance have no significant effect, as they do not exert sufficient pressure on management to engage in earnings management. Theory and Practical Implications - The findings indicate that agency theory can explain the relationship between profitability and earnings management but does not fully explain the effects of leverage and tax avoidance. Companies should strengthen earnings-reporting oversight, particularly when profitability increases, to ensure reliable financial information. Novelty - This study examines profitability, leverage, and tax avoidance in insurance subsector companies characterized by reporting involving estimates, technical reserves, and claim liabilities, providing empirical evidence of their relationship with earnings management.